Evaluasi Usulan Pembangunan Bandar Udara Wirasaba di Purbalingga Jawa Tengah - Susanti Susanti (WARTA ARDHIA, 2015)
Wirasaba Airport is a military airport operated under responsibily of the Indonesian Air Force. This airport located in Purbalingga, Central Java. In order to increase economic potential and tourisme in this area, local government of Purbalingga proposed the change function of Wirasaba Airport becoming Civil Enclave Airport. Civil Enclave Airport is a military airport which also provide civil aviation services. This study used a qualitative descriptive analysis method. The results shows that development of Wirasaba Airport is not a priority based on several considerations. First consideration is the fact that Wirasaba Airport is not included in Minister of Transportation Decree No. Km 69 year of 2013 about the Airport Master Plan. Beside that, land vailability in this area is also complicated. Surrounding area in wirasaba Airport is belong to Indonesian Air Force. Furthermore, this airport does not meet criteria of airport coverage services. The national requirement state that airport coverage service in Java Island is 200 km away to cover 100 km for each nearest airport. The nearest aiport from Wirasaba Airport are Ahmad Yani Airport in Semarang and Tunggu Wulung Airport in Cilacap. The distance between Wirasaba Airport to those closest airport less than 200 km and passenger demand in Central Java Area has not show the over capacity trend. Keywords: airport development, wirasaba, evaluation, central java. Bandar Udara Wirasaba adalah Bandar Udara militer milik TNI-AU yang berlokasi di Purbalingga Jawa Tengah. Pada tahun 2015 terdapat usulan dari Pemerintah Daerah untuk menjadikan Bandara Wirasaba sebagai Bandara enclave sipil, atau bandara militer yang dapat digunakan sebagai bandara sipil, hal ini bertujuan untuk meningkatkan potensi ekonomi serta pariwisata di daerah tersebut. Kajian ini menggunakan metode analisis deskriptif kualitatif. Hasil evaluasi adalah Bandara Wirasaba belum dapat menjadi prioritas untuk pembangunan bandar udara Nasional dengan pertimbangan diantaranya adalah tidak termasuk dalam Rencana Induk Bandar Udara yang ditetapkan oleh Menteri Perhubungan, masalah kepastian lahan dengan TNI-AU yang membutuhkan kejelasan, tidak termasuk kriteria dalam cakupan pelayanan bandara dalam Tatanan Kebandarudaraan Nasional, yang mengisyaratkan jarak antar dua bandara dalam Pulau Jawa dan Sumatera adalah 200 km dengan cakupan pelayanan masing-masing 100 km. Sedangkan bandara terdekat yaitu Ahmad Yani di Semarang dan Bandara Tunggul Wulung di Cilacap kurang dari 200 km, dan permintaan jasa angkutan udara di wilayah Jawa Tengah belum menunjukkan trend over capacity. Kata kunci: Pembangunan bandar udara, wirasaba, evaluasi, Jawa Tengah.